Molecular Mechanisms for Vascular Development and Secondary Cell Wall Formation - Yang, Jung Hyun; Wang, Huanzhong (Frontiers in Plant Science, 2016)
Vascular tissues are important for transporting water and nutrients throughout the plant and as physical support of upright growth. The primary constituents of vascular tissues, xylem, and phloem, are derived from the meristematic vascular procambium and cambium. Xylem cells develop secondary cell walls (SCWs) that form the largest part of plant lignocellulosic biomass that serve as a renewable feedstock for biofuel production. For the last decade, research on vascular development and SCW biosynthesis has seen rapid progress due to the importance of these processes to plant biology and to the biofuel industry. Plant hormones, transcriptional regulators and peptide signaling regulate procambium/cambium proliferation, vascular patterning, and xylem differentiation. Transcriptional regulatory pathways play a pivot role in SCW biosynthesis. Although most of these discoveries are derived from research in Arabidopsis, many genes have shown conserved functions in biofuel feedstock species. Here, we review the recent advances in our understanding of vascular development and SCW formation and discuss potential biotechnological uses.